Civil service management and corruption: What we know and what we don't. (18th April 2018) - Meyer‐Sahling, Jan‐Hinrik; Mikkelsen, Kim Sass; Schuster, Christian
Abstract : Numerous studies have linked a range of economic, social, and institutional variables with corruption in government. Yet, most of this literature overlooks the management of public officials themselves. This is a relevant omission: almost all corrupt exchanges involve public officials. This article reviews studies—36 in total—that do address civil service management and anti‐corruption. It finds that prior works assess a narrow set of civil service management structures. Meritocratic recruitment and, less robustly, pay levels have been associated with lower corruption. By contrast, robust evidence on how corruption relates to other established public personnel management areas—such as distinct pay structures (rather than levels), promotion, transfer, and job stability practices—is largely unavailable. The article thus calls for research assessing the effects of a broader set of civil service management practices to gain a deeper understanding of corruption, and how to curb it.